Market Opportunities for New Sauerkraut Products - Sandra Cuellar; Wen-fei Uva; John M. Roberts (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2005)
Production and processing of head cabbage has a significant economic importance for New York State agriculture. New York produces about one-fourth of the total U.S. head cabbage output, with 79 percent destined to the fresh market. In the U.S., New York is the number one producer of fresh head cabbage (with a market share of 22 percent) and is number two, after Wisconsin, in the production of sauerkraut, with a market share of 39 percent (Lucier and Lin, 2002). During the past decade (1991 to 2001), production of fresh head cabbage and sauerkraut in New York State increased 61 percent and 23 percent, respectively. During the same period, per capita consumption of fresh cabbage increased from 8.2 pounds to 8.8 pounds (an increase of 7.3 percent), while consumption of sauerkraut stayed stable at around 1.3 pounds (a decrease of between 2.2 to 2.3 pounds from the 1960s to 70s levels (USDA, 2004). The consumption trends of fresh head cabbage and sauerkraut clearly reflect today`s consumers` food preferences, which are strongly determined by an increasing desire and interest in both fresher and more complex and exciting food products. The incorporation of fresh cabbage to bagged salads is thought to be a major contributing factor to the observed increase in consumption of fresh head cabbage. On the other hand, sauerkraut sold and consumed today in the U.S. market is not that different from the sauerkraut made a hundred years ago and is appreciated mostly by older consumers and little by younger consumers.
Keywords: 330; Verarbeitetes Obst und Gemüse; Markt; Konsumentenverhalten; USA